A reforma trabalhista e a (des)construção do Direito do Trabalho no Brasil: uma análise da conjuntura da aprovação da Lei 13.467/2017 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The present survey had as object of investigation the conjuncture in which the approval of the labour reform in Brazil in 2017, instrumented by the approval of Law nº 13.467 / 2017, was affected. The changes promoted in the legal system of regulation of labour relations, disseminated by its advocates and actors involved with the approval of the reform as necessary modernization to leverage the economy and take the country out of the crisis that it has been facing since the year 2014. However, the discussion surrounding the need for labour reform emerged in the country in the early 1990s and many attempts have been made to change labour legislation since then, but nothing had been as profound and extensive as the changes made with the 2017 reform. New legislation labour represents an urgent interpretive challenge, given its strong social and economic repercussion in the lives of millions of Brazilians who depend on their workforce to survive. The research had an interdisciplinary character, not being restricted, furthermore, to the domains of Labour Law, presented the economic, social and political context of the event. The main questions that moved the research were: what was the situation in which the approval of Law 13467/2017 occurred? This would have facilitated discussion and approval of the project? What were the real interests at stake? The analysis kept a special focus on the National Congress, the stage of the event, and investigated previous aspects that influenced the approval of the reform, the exogenous factors that propelled it, the actors that promoted it, and the correlation of forces between them. In order to reach the proposed objective, a qualitative research was carried out, through bibliographical and documentary research and, later, the processing and analysis of the collected data adopting as main methodology the conjuncture analysis.
Keywords: reforma trabalhista; Lei nº 13.467/2017; direito do trabalho; análise de conjuntura; labour reform; Law nº 13.467/2017; labour law; analysis of conjuncture; CNPQ::CIENCIAS SOCIAIS APLICADAS